improving the efficiency of a motor transport enterprise’s activity using labor resources - L. I. Rogavichene (Вестник СибАДИ, 2017)
The article is devoted to the problem of improving the efficiency of transport enterprises’ activity by problems solving in personnel management. The considerable attention is paid to the main factors of improving efficiency of motor transport enterprise’s activity in the aspect of using labour resources. The author concludes that there is required a mathematical assessment of the level of influencing determinants of improving efficiency of motor transport enterprise’s actibity to determine the functional dependence of the economic results of the motor transport enterprise’s activity and analyzed factors.